Når ord sier mer enn kunst : En studie av museers arbeid med ord og titler i samlingen som framstår som støtende - Dahl,Agnes Karoline (2023)
This master's thesis is about how three museums, the Glyptoteket in Copenhagen, the National Museum in Oslo and the Munch Museum in Oslo, have in each case shown their work with difficult history and how newspapers have portrayed the debate related to the museums' actions. Using critical discourse analysis and authorized heritage discourse, I have carried out a case study in which I examine the museums as managers of cultural heritage and identity. I point to the different factors in the work at the various museums and in conclusion give a proposal for how to combine the museums work to communicate difficult history to create a broader understanding of the past.
Keywords: Museums; difficult history; racism; cultural heritage; museologi; kulturarv